Pengaruh Komunikasi Dan Motivasi Terhadap Semangat Kerja Pegawai Honorer Kantor Desa Paya Bakung Kecamatan Hamparan Perak Kabupaten Deli Serdang - Muhammad Fajar Syahputra (JOURNAL ECONOMICS AND STRATEGY, 2024)
The purpose of this research is to ascertain how inspiration and correspondence affect the morale of privileged representatives working in the Paya Bakung Town Office in the Hamparan Perak Region. As mentioned by the examination goals, the exploration data came from surveys, opinions, and related writing research. The F and T tests, in particular, are two of the several straight relapse with speculation tests used in the investigative process. 35 respondents took part in the exams, which included unintentional examination techniques. The results demonstrated that the elements of Inspiration and Correspondence had a significant influence on the Resolve of Privileged Workers at the Paya Bakung Town Office, Hamparan Perak Locale, Store Serdang Regime, either completely or partially.